The Impact of Pepper Prices Falling on the Desire and Intensity of Pepper Cultivation in Bangka Belitung Islands - Atmaja, Eddy Jajang Jaya; Setiawan, Iwan (JIA (Jurnal Ilmiah Agribisnis) : Jurnal Agribisnis dan Ilmu Sosial Ekonomi Pertanian, 2022)
The pepper prices have kept falling since 2015, but farmers still cultivate pepper in Bangka Belitung Province. However, the impact of pepper prices falling on the Farmer' desires and intensity of pepper cultivation has never been known yet. This research was conducted to find out farmers' desire to cultivate pepper and to know the intensity of pepper cultivating caused by pepper price falling. The research survey methods were held for six months from May to November 2020 in six regions in the Province of Bangka Belitung. The survey method analyzes falling pepper prices' impact on the Farmer's desires and pepper cultivation intensity. The data is collected from six districts of Bangka Belitung Islands by involving 180 samples. The location of the research setting is purposive. The total sampling in each region was 30 farmers, so the sampling in six areas was 180 farmers. All data were analyzed using descriptive analysis. In Bangka Belitung Province, primarily farmers 35,5 – 47,5 years old and most educated elementary school thinking that their pepper production would fulfill their basic needs. Even most farmers (83 percent) think confident in 2020, but the decline in pepper price makes most of them reluctant to cultivate pepper. This study indicates that farmers who reach the age of 47,5 keep losing their involvement in pepper farming. Regardless, most farmers (83 percent) say optimistic in one and two years. The pepper prices would be increased from 2020, but the falling of pepper affected half of the farmers not willing to cultivate peppers. Palm oil, rubber, and cassava were the selection to replace peppers. These plants have more advantages for farmers because pests and diseases not like pepper are challenging to cultivate. If the prices of pepper increase, the farmers will produce again. Pepper prices keep falling, regardless of the Government's efforts to recapture the popularity of Lada Bangka (Muntok White Pepper, MWP). This falling pepper price continues to cause the decreasing of farmers' desire and intensity in cultivating pepper. Through all this research, recommended to Government not only gave significant helping as production facilities and quality seeds, but to give also certainty for buying and pepper prices profitable and reasonable for farmers as producer pepper in Bangka Belitung Province.